Implementasi Augmented Reality (AR) Sebagai Media Pengenalan Aksara Ka Ga Nga Rejang Lebong Berbasis Android - Anisya Sonita; Arif Susanto (Penerbit Jurnal Indonesia, 2022)
Computers are widely used to assist in completing human work, jobs that previously could only be done manually, but with the rapid development of technology the work can be done with the help of computers which is certainly very easy and can save time. And one of the computer technologies that are currently being developed is Augmented Reality. The script in the ulu or kaganga script is inscribed on bamboo slats commonly called gelumpai or written on bark called kahas, gelumpai or kahas, for example in the form of letters that are tilted to the right and broken. The Kaganga script is the name of a collection of several related scripts used by ethnic groups and cultures in southern Sumatra. The scripts belonging to this group include the Rejang, Kerinci, Lampung, Rencong scripts and others. Batak script or Batak letters are also related to this group. Augmented Reality technology can help students in establishing information connections between the real world and the virtual world more easily, as a form of perspective in increasing learning motivation.